Memantine Attenuates Cocaine and neuroHIV Neurotoxicity in the Medial Prefrontal Cortex - Du, Congwu; Hua, Yueming; Clare, Kevin; Park, Kicheon; Allen, Craig P.; Volkow, Nora D.; Hu, Xiu-Ti; Pan, Yingtian (Frontiers in Pharmacology, 2022)
Individuals with substance use disorder are at a higher risk of contracting HIV and progress more rapidly to AIDS as drugs of abuse, such as cocaine, potentiate the neurotoxic effects of HIV associated proteins including, but not limited to HIV-1, trans-activator of transcription (Tat) and the envelope protein Gp120. Neurotoxicity and neurodegeneration are hallmarks of HIV-1-associated neurocognitive disorders (HAND) which are hypothesized to occur in part secondary to excitotoxicity from NMDA induced neuronal calcium dysregulation, which could be targeted with NMDA antagonist drugs. Multiple studies have examined how Gp120 affects calcium influx and how cocaine potentiates this influx; however, they mostly focused on single cells and did not analyze effects in neuronal and vascular brain networks. Here, we utilize a custom multiwavelength imaging platform to simultaneous study neuronal activity (detected using genetically-encoded Ca2+ indicator, GcaMP6f expressed in neurons) and hemodynamic changes (measured by total hemoglobin and oxygenated hemoglobin within the tissue) in the prefrontal cortex (PFC) of HIV-1 Tg rats in response to cocaine and evaluated the effects of the selective NMDA antagonist drug memantine on cocaine and HIV neurotoxicity compared to non-HIV-1 Tg animals (controls). Our results show that memantine improved cocaine-induced deficit in cerebral blood volume while also attenuating an abnormal increase of neuronal calcium influx and influx duration in both control rats and HIV-1 Tg rats. Cocaine-induced neuronal and hemodynamic dysregulations were significantly greater in HIV-1 Tg rats than in control rats. With memantine pretreatment, HIV-1 Tg rats showed attenuated cocaine’s effects on neuronal and hemodynamic responses with responses similar to those observed in control rats. These imaging results document an enhancement of neuronal Ca2+ influx, hypoxemia and ischemia with cocaine in the PFC of HIV-1 Tg rats that were attenuated by memantine pretreatment. Thus, the potential utility of memantine in the treatment of HAND and of cocaine-induced neurotoxicity deserves further investigation.